2020
DOI: 10.1371/journal.pmed.1003289
|View full text |Cite
|
Sign up to set email alerts
|

Age and the association between apolipoprotein E genotype and Alzheimer disease: A cerebrospinal fluid biomarker–based case–control study

Abstract: Background The ε4 allele of apolipoprotein E (APOE) gene and increasing age are two of the most important known risk factors for developing Alzheimer disease (AD). The diagnosis of AD based on clinical symptoms alone is known to have poor specificity; recently developed diagnostic criteria based on biomarkers that reflect underlying AD neuropathology allow better

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 46 publications
4
53
0
Order By: Relevance
“…The ε4 allele of the Apolipoprotein E (APOE) gene is the strongest genetic risk factor for late onset Alzheimer's disease (AD) [1]. Around 25% of the Caucasian population carries at least one ε4 allele [2], with a 3-fold increased risk of AD for heterozygotes and a nearly 15fold increased risk for homozygotes compared to the ε3 homozygotes, the most common genotype [3]. APOE ε2 is less common and appears to have a protective effect on AD [4].…”
Section: Introductionmentioning
confidence: 99%
“…The ε4 allele of the Apolipoprotein E (APOE) gene is the strongest genetic risk factor for late onset Alzheimer's disease (AD) [1]. Around 25% of the Caucasian population carries at least one ε4 allele [2], with a 3-fold increased risk of AD for heterozygotes and a nearly 15fold increased risk for homozygotes compared to the ε3 homozygotes, the most common genotype [3]. APOE ε2 is less common and appears to have a protective effect on AD [4].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the predictive model with driving behaviour and age alone achieved an F1 score of 0.88 (95% CI 0.86–0.91), and the model with driving behaviour, age, and APOE ε4 status achieved an F1 score of 0.91 (95% CI 0.89–0.94). This improvement is unsurprising since age and APOE ε4 are among the strongest risk factors for AD [ 36 ]. Others have shown that the ability of novel AD biomarkers to predict preclinical AD (generally indicated by abnormality of PET or CSF amyloid biomarkers) may be improved by including age and APOE ε4 status in models [ 34 , 37 , 38 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…CSF t-tau, p-tau, Abeta 42, and Abeta 40 were quantified using ELISA kits from Fujirebio (Fujirebio, Ghent, Belgium). The established lab-specific cut-offs indicating pathological levels t-tau > 449 pg/ml, p-tau > 60 pg/ml, Abeta 1-42 < 450 pg/ml, and Abeta ratio [(abeta1-42/abeta1-40)*10)] <0.975 were applied as previously reported [ 30 ]. Test performers were blind to clinical information and clinical investigators vice versa.…”
Section: Methodsmentioning
confidence: 99%